Enamel defects and caries prevalence in preterm children aged 5-10 years in Dubai. Issue 1 (1st January 2020) - Alshehhi, Anood; Al Halabi, Manal; Hussein, Iyad; Salami, Anas; Hassan, Amar; Kowash, Mawlood
ABSTRACT: Background : Enamel defects (EDs) are commonly reported dental findings in preterm/low birthweight children. EDs potentially increase caries susceptibility. Aim : To assess the prevalence of EDs and dental caries in a group of preterm children (aged 5–10 years) in Dubai, United Arab Emirates (UAE). Methodology : A retrospective cohort study of medical records of 62 preterm children (mean age 8.1 ± 1.54) and 62 full-term children (mean age 8.1 ± 1.73) of both genders born in a UAE children's hospital were studied. These children were dentally assessed for EDs and caries by a calibrated examiner. Results : EDs were 4.34 times more prevalent among preterm children [odd ratio (OR) = 4.338, CI 95% [2.010–9.366]. The prevalence of EDs in the pre-term group was 58.15%, significantly higher (P < 0.01) than the full-term control group (24.2%). Birth weight, intubation and type of delivery were statistically significant factors contributing to EDs. In the primary dentition, the mean dmft was 4.61 ± 4.30, while in the permanent dentition DMFT was 0.38 ± 0.99. There was a statistically significant difference in permanent teeth caries experience amongst pre-term children compared to the full-term control as measured by DMFT (P = 0.008). Conclusion : EDs and dental caries in permanent dentition in the pre-term group were significantly higher than the full-term group.